The Potential of the Bebak Wall Protection Technique on Increasing Construction Stability and Material Bond Strength - Pradipto, Eugenius; Afif, Nabila (ARSITEKTURA, 2020)
Bebak, the local building material of East Nusa Tenggara, has long been used as the primary building material, especially as wall material. However, bebak wall construction commonly used today is not yet ideal in terms of its material protection and function. Bebak is a relatively quick damage construction due to termites, which eventually causes the enclosed space's thermal conditions less comfortable. This research is part of the quality improvement program of healthy housing in that region, which focuses on bebak wall protection by plastering the wall with concrete plaster. Two scale models were examined; a wall plastered only on one side, and a wall plastered on both sides. By using a simple construction approach, the research aims to evaluate the bebak protection technique's effects on the construction stability and the bond strength between the bebak composite wall materials. The results of visual evaluations revealed that single-sided plaster on bebak walls could maintain the construction stability and the bond strength of the composite material better than the double-sided one. Furthermore, the evaluation also reveals additional benefits of the plastered walls for the users, such as adaptability and simplicity of modular wall replication to build affordable healthy housing.